The effect of SGLT2i on in-hospital acute heart failure risk in acute myocardial infarction patients—a retrospective study - Zhu, Yi; Zhang, Jia-li; Jin, Hong; Ji, Yuan; Wang, Fang-fang (Frontiers in Cardiovascular Medicine, 2023)
Background and aims The roles of sodium-glucose cotransporter 2 inhibitor (SGLT2i) in acute heart failure (AHF) risk after acute myocardial infarction (AMI) remain unclear. In this study, we explored the correlation between SGLT2i administration and short-term in-hospital AHF risk in AMI patients. Methods This single-center, retrospective, and observational study included 990 AMI patients comprising 386 non-ST-segment elevation myocardial infarction (NSTEMI) and 604 segment elevation myocardial infarction (STEMI) patients enrolled from January 2019 to March 2022. Demographic information, clinical characteristics, medical treatment, and laboratory examination results during hospitalization were extracted from an electronic medical record system. The primary outcome was defined as all-cause AHF during hospitalization. Results In NSTEMI patients, a significantly lower proportion received SGLT2i treatment in the AHF group compared with the non-AHF group. During hospitalization, SGLT2i significantly reduced brain natriuretic peptide levels both in STEMI and NSTEMI patients. Multivariate logistic regression and stratification analyses suggested that SGLT2i is associated with reduced in-hospital AHF risk, and has a strong protective effect against AHF in NSTEMI patients with hypertension. Furthermore, SGLT2i significantly reduced the risk of in-hospital AHF for both patients with diabetes and non-diabetes. Conclusions SGLT2i can reduce the risk of AHF in AMI patients during hospitalization.